MuDeL: A Language and a System for Describing and Generating Mutants - Simão, Adenilso da Silva; Maldonado, José Carlos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de Software, 2001)
Mutation Testing is an approach for assessing the quality of a test case suite by analyzing its ability in distinguishing the product under test from a set of alternative products, the so-called mutants. The mutants are generated from the product under test by applying a set of mutant operators, which produce products with slight syntactical differences. The mutant operators are usually based on typical errors that occurs during the software development and can be related to a fault model. In this paper, we propose a language — named MuDeL — for describing mutant operators aiming not only at automating the mutant generation, but also at providing precision and formality to the operator descriptions. The language was designed using concepts that come from transformational and logical programming paradigms, as well as from context-free grammar theory. The language is illustrated with some simple examples. We also describe the mudelgen system, developed to support this language.